(untitled) (PERcursos Linguísticos, 2025)
This article investigates the intersections between linguistic education and decoloniality, based on Quarto de Despejo by Carolina Maria de Jesus. Grounded in critical literacy theories (Jordão, 2012; Freire, 1980) and decolonial pedagogy (Quijano, 2009; Dussel, 1993), the study argues that literature can serve as an essential tool for reflecting on structural inequalities and valuing marginalized narratives. Through a pedagogical project conducted with high school students, connections were explored between the experiences portrayed by Carolina and local realities, proposing educational practices that foster (linguistic) critical emancipation and social awareness. Furthermore, the analysis engages with ethnographic perspectives (Clifford & Marcus, 1986) and the redefinition of plural knowledge systems (Duboc & Gattolin, 2015). The article highlights the importance of educational practices that transcend modern paradigms and integrate diverse epistemologies, promoting resistance to inequalities and social transformation.